2017
DOI: 10.1089/rej.2017.1930
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of Cardiac Tissue Developed from Reprogrammed Aged Somatic Cells

Abstract: Induced pluripotent stem cells (iPSCs) derived via somatic cell reprogramming have been reported to reset aged somatic cells to a more youthful state, characterized by elongated telomeres, a rearranged mitochondrial network, reduced oxidative stress, and restored pluripotency. However, it is still unclear whether the reprogrammed aged somatic cells can function normally as embryonic stem cells (ESCs) during development and be rejuvenated. In the current study, we applied the aggregation technique to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In the research on aging a great attention is paid to the cells and tissues with high mitotic index (MI). This parameter allows such cells to retain a high regenerative potential and make them a target for experiments aimed at rejuvenation [40,41,42,43]. From our point of view, only influencing the epigenetic mechanisms of cells with high MI is clearly insufficient to achieve true rejuvenation of the Mammalia organism [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the research on aging a great attention is paid to the cells and tissues with high mitotic index (MI). This parameter allows such cells to retain a high regenerative potential and make them a target for experiments aimed at rejuvenation [40,41,42,43]. From our point of view, only influencing the epigenetic mechanisms of cells with high MI is clearly insufficient to achieve true rejuvenation of the Mammalia organism [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both groups injected with iPSC-derived vascular progenitor cells showed comparable, improved hindlimb revascularisation compared with non-treated animals ( 46 ). Another study showed that cardiac tissue of iPSC-derived chimeric mice, with iPSCs derived from the bone marrow of 2- and 18-month-old mice, showed no difference in telomere length or mitochondrial gene expression and no upregulation of p16 nor p53 was detected between both age groups ( 47 ).…”
Section: Functionality and Ageing Of Ipscs And Ipsc-derived Cells—howmentioning
confidence: 99%
“…To verify if there are any altered response of GFP transgenic mice to TBI, a mouse model for RAR (Yonezawa Effect) was adopted and applied to this work using C57BL/6N-GFP mice, the first engineered GFP transgenic mice in the world with applications in a wide range of research fields including radiation biology. 25 , 51 - 63 RAR is a phenomenon that pre-exposure to a low priming dose reduces the biological effects of a subsequent higher challenge dose. Since the discovery of RAR, 64 it has been demonstrated in a variety of biosystems from simple prokaryotes to higher eukaryotes including mammalian animals with varied endpoints including cell death and bone marrow death.…”
Section: Discussionmentioning
confidence: 99%